2006
DOI: 10.1002/jbt.20109
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione‐enhancing agents protect against steatohepatitis in a dietary model

Abstract: Nonalcoholic fatty liver (NAFL) and steatohepatitis (NASH) may accompany obesity, diabetes, parenteral nutrition, jejeuno-ileal bypass, and chronic inflammatory bowel disease. Currently there is no FDA approved and effective therapy available. We investigated the potential efficacy of those agents that stimulate glutathione (GSH) biosynthesis on the development of experimental steatohepatitis. Rats fed (ad libitum) amino acid based methionine-choline deficient (MCD) diet were further gavaged with (1) vehicle (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 30 publications
2
57
0
1
Order By: Relevance
“…The results of our studies suggest that diet, including anti-oxidant supplements and maintenance of cellular GSH levels, may be important in preventing the development of chronic non-alcoholic liver disease (CNLD), non-alcoholic steatohepatitis, and hepatocellular carcinoma. The importance of such protection was recently emphasized by a report showing that glutathione-enhancing agents provided protection against steatohepatitis in a rat dietary model of this disease (Oz et al, 2006). Our studies implicate insulin signaling pathways involving PI3K and its downstream effectors in the insulin-mediated regulation of drug metabolizing enzymes including CYP2E1, alpha-class GSTs, mEH and GCL catalytic subunit.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…The results of our studies suggest that diet, including anti-oxidant supplements and maintenance of cellular GSH levels, may be important in preventing the development of chronic non-alcoholic liver disease (CNLD), non-alcoholic steatohepatitis, and hepatocellular carcinoma. The importance of such protection was recently emphasized by a report showing that glutathione-enhancing agents provided protection against steatohepatitis in a rat dietary model of this disease (Oz et al, 2006). Our studies implicate insulin signaling pathways involving PI3K and its downstream effectors in the insulin-mediated regulation of drug metabolizing enzymes including CYP2E1, alpha-class GSTs, mEH and GCL catalytic subunit.…”
Section: Resultsmentioning
confidence: 54%
“…Reprinted from Kim SK, Abdelmegeed MA and Novak RF, J Pharmacol Exp Ther. 316, 1255-1261, 2006, with permission. Insulin effect on GCLC protein (A), GCLC mRNA (B), GCL activity (C), and GSH (D) levels in primary cultured rat hepatocytes.…”
Section: Figmentioning
confidence: 99%
“…Similarly, oral administration of PTCA provided protection against steatohepatitis by attenuating the expression of deleterious proinflammatory and fibrogenic genes in a dietary rat model. 31 Other studies showed that PTCA significantly increased GSH biosynthesis in cultured rat lens compared with untreated controls 32 and prevented naphthalene-induced experimental cataracts in mice. 33 In this study, PTCA-treated mice had significantly normalized levels of inflammatory cytokines (IL-6 and IL-12), acute protein SAA, colon lesions, with higher levels of blood and hepatic GSH, and lower GSSG concentrations compared with other treated and untreated DSS animals.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, two glutathione-replenishing agents, S-adenosylmethionine and 2(RS)-npropylthiazolidine-4(R)-carboxylic acid (i.e. an L-cysteine pro-drug), were shown to protect against steatohepatitis induced by the methionine-choline deficient diet; however, these agents did not prevent alterations in GSH and GSSG levels in response to steatohepatitis [88]. Nonetheless, increased GSSG concentrations were found in the blood of NASH patients suggesting defects in glutathione metabolism [89].…”
Section: Mitochondria Dysfunction In Fatty Liver Diseases -Bioenergetmentioning
confidence: 99%